Technical Assessment of Urban Drainage Performance in Inundation-Prone Areas Around Mataram and West Lombok - Muhammad Khalis Ilmi; Swahip Swahip; Ari Ramadhan Hidayat; Rajabi Mubarak; Ringgi Puteri Samengasbumi; Chelse Putri Apriani; Elsa Juniastasya; Abdullah Faqih; Mirsodir Rosyid; Mohamad Iqbal Abdullah; Muhamad Rizal (Journal of Civil Engineering and Planning (JCEP), 2026)
The problems of flooding and waterlogging in urban areas have become a critical issue in urban infrastructure development, particularly in the city of Mataram and West Lombok Regency. Therefore, effective drainage system management is a key element in urban flood risk management. This study aims to assess the performance of urban drainage systems in residential areas and along highways based on Regulation of the Minister of Public Works and People’s Housing (Permen PUPR) No. 12/PRT/M/2014. The results show that the percentage of drainage channels that “failed” due to overtopping, overflow, or ponding (Qcapacity<Qdesign) was predominantly found in residential areas, with the highest percentage occurring in the primary drainage network. This indicates that the risk of flooding is higher in primary drainage networks because these networks handle a greater volume of wastewater compared to secondary and tertiary drainage networks. Based on administrative regions, the drainage performance of the drainage systems spread across West Lombok is worse than that of the city of Mataram. Based on the results of surveys and mapping of existing conditions at the study site, several problems were identified, including sedimentation, vegetation growth, and narrowing in several channel segments, which have the potential to reduce flow capacity and cause.